Numerical simulation of fluids structure interaction (FSI) in asymmetric abdominal aortic aneurysm (AAA) using adina - Nurul Amira Zainal, 1988-; Norzieha Mustapha, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2012